Operative delivery in women with benign uterine tumors - В. С. Ольшевський; О. В. Ольшевська (Publishing House TRILIST, 2019)
Objective of the study: to determine the role of operative delivery in the childbirth tactics for women with benign uterine tumors based on the identification of pathogenetically substantiated criteria for operative birth, to prevent obstetric and perinatal complications. Materials and methods. In 110 women with uterine leiomyoma (LM) - 77 (70.0%) with one node (Group 1) and 33 (30.0%) with multiple nodes (Group 2) delivery tactics were defined. For this purpose, the type of LM, the location of the nodes relative to the placenta, complications of pregnancy, childbirth were revealed and analyzed. Study results and discussion. The revealed coincidence of the location for І-ІV types LM nodes and placenta in 33 (42.86%) cases of one node and in 23 (69.70%) of multiple LM caused complications in the gestational period: placental insufficiency - in 44.16% and 45.45%; threat of interruption - in 30.30% and 5.96%; partial detachment of the placenta - in 18.18% and 27.27%; myomectomy - in 7.70% and 15.15%; fetal distress - in 31.17% and 36.36%; the threat of premature birth - in 24.68% and 24.24% of cases with the one node and multiple LM respectively and necessitated the determination of delivery tactics. Caesarean section was done in 42 (38.18%) cases: in 28 (36.36%) women with one node and in 14 (42.42%) with multiple nodes. The tendency to a higher frequency of operative delivery with multiple LM is due to the greater frequency of coincidence of the nodes location and placenta and pregnancy complications. Urgent delivery was made in 28.57% cases with one node of LM and in 14.28% with multiple nodes due to premature detachment of the placenta and bleeding, fetal distress. A smaller percentage of urgent operative delivery is due to an increase frequency of elective caesarean section for LM. Conclusions. The coincidence of II-IV types LM node/nodes and placenta location is considered to be a pathogenetic factor in placental insufficiency, placental abruption in the gestational period and during childbirth, bleeding, fetal distress, and the prognostic criterion for obstetric and perinatal complications. Among pathogenetically substantiated criteria for operative delivery along with other factors consider: coincidence of the location of the placenta and II-IV types LM node or multiple І-ІV types LM nodes; myomectomy. Presence of these criteria determines the planned caesarean section by the method of choice in the childbirth tactics for women with LM.